The Relationship of Corporate Social Responsibility and Firm Performance: A Bibliometric Overview - Deepa Sharma; Suman Chakraborty; Ashwath Ananda Rao; Lumen Shawn Lobo (SAGE Open, 2023)
Corporate social responsibility and its relationship with firm performance have been the focus of studies concerning the area of social responsibility of companies over the last four decades. The area has undergone significant progressions and shifts over time. There is a tremendous interest among the researchers in analyzing the relationship between corporate social responsibility and firm performance, as evident by the increasing surge in the research publications in this domain, especially since 2010. This study intends to highlight the knowledge expansion and research dispersion in the broad area concerning corporate social responsibility and its effect on firm performance. For this purpose, the research articles published in the Scopus database from 1987 to 2021, covering 34 years, have been taken to perform a bibliometric analysis. The study explains the descriptive trend of research publications focusing on performance indicators and uses a thematic evolution tool to highlight the major themes. The results of the bibliometric studies reveal that the focus of research encompasses the dimensions of sustainability, strategic management, institutional pressures, disclosure, and corporate social responsibility reporting. Based on these dimensions, the paper presents insights into the existing studies and offers the scope for future research.